(untitled) (Journal of the College of Basic Education, 2022)
The principles proclaimed in the Charter of the United Nations constitute recognition of the inherent dignity and equal and inalienable rights of all members of the human family, which is the basis of freedom, justice and peace in the world. It advances social progress and raises the standard of life in an atmosphere of freedom. It was stated in the Universal Declaration of Human Rights in the two International Covenants on Human Rights that every human being has the right to enjoy all the rights and freedoms contained in those instruments, without any kind of discrimination on grounds of race, color or sex. language, religion, political or other water, national origin, wealth, birth or any other status, and social status